Efektivitas Pemijatan Akupresur Titik P6 & ST36 Dengan Time Reminder Terhadap Emesis Gravidarum Pada Ibu Hamil Trimester 1 - Ega Shafira Pradanawati (2021)
Emesis gravidarum is a general condition experienced by pregnant women, especially pregnant women of the first trimester. However, there are still pregnant women who think this condition is nothing to worry about. If the condition of emesis gravidarum is not treated until the next trimester, it can be dangerous for the mother and fetus. Therefore, this study aims to find out the effectiveness of acupressure massage points P6 and ST36 with time reminder on the reduction of emesis gravidarum on pregnant women of the first trimester. This study used one group pretest-posttest design with a Purposive Sampling technique of 27 samples. Based on the statistical test using paired t-test, the result of p-value = 0.000 was obtained. This is interpreted that there is the effectiveness of acupressure massage points P6 and ST36 with time reminder on the reduction of emesis gravidarum on pregnant women of the first trimester with the difference of mean value before and after the intervention is 3. Acupressure massage points P6 and ST36 is a non-pharmacological treatment that can reduce the condition of emesis gravidarum on pregnant women of the first trimester.